2014
DOI: 10.5433/1679-0359.2014v35n1p277
|View full text |Cite
|
Sign up to set email alerts
|

Secagem de grãos residuais de urucum por exposição direta ao sol combinada com secagem em secador acumulador de calor

Abstract: ResumoO processo de extração do pigmento bixina resulta em uma grande quantidade de grãos residuais de urucum. A maior parte desse material é descartada, mas é possível aproveitá-lo incorporando-o em rações para animais e na alimentação humana. Neste trabalho, objetivou-se secar grãos residuais de urucum utilizando energia solar. Os grãos foram divididos em dois lotes, um com óleo, reproduzindo as condições dos grãos após a extração oleosa de bixina e outro lote sem óleo. As secagens foram realizadas durante o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
2
0
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 14 publications
1
2
0
1
Order By: Relevance
“…The effective diffusivity in solar dryer was 1.47 × 10 -9 , 1.20 × 10 -9 and 0.63 × 10 -9 m 2 s -1 for the thicknesses of 11.95, 8.06 and 4.11 mm, respectively, whereas the drying by exposure to the sun led to values of 1.29 × 10 -9 , 1.11 × 10 -9 and 0.54 × 10 -9 m 2 s -1 for the respective thicknesses of 11.95, 8.06 and 4.11 mm. In all experiments the values were within the range from 10 -11 to 10 -9 m 2 s -1 mentioned by Madamba et al (1996), for the diffusivity of foodstuffs, and close to the values found by Santos et al (2014b) and Dhalsamant et al (2017), when drying residual grains of annatto and potato cylinders using solar energy, respectively. For the same layer thickness, it was observed that the samples dehydrated in the solar dryer had the highest effective diffusion coefficients, being positively correlated with the high temperatures of the solar dryer, which increased the vibrational state of the water molecules (Mghazli et al, 2017).…”
Section: Moisture Effective Diffusivitysupporting
confidence: 87%
“…The effective diffusivity in solar dryer was 1.47 × 10 -9 , 1.20 × 10 -9 and 0.63 × 10 -9 m 2 s -1 for the thicknesses of 11.95, 8.06 and 4.11 mm, respectively, whereas the drying by exposure to the sun led to values of 1.29 × 10 -9 , 1.11 × 10 -9 and 0.54 × 10 -9 m 2 s -1 for the respective thicknesses of 11.95, 8.06 and 4.11 mm. In all experiments the values were within the range from 10 -11 to 10 -9 m 2 s -1 mentioned by Madamba et al (1996), for the diffusivity of foodstuffs, and close to the values found by Santos et al (2014b) and Dhalsamant et al (2017), when drying residual grains of annatto and potato cylinders using solar energy, respectively. For the same layer thickness, it was observed that the samples dehydrated in the solar dryer had the highest effective diffusion coefficients, being positively correlated with the high temperatures of the solar dryer, which increased the vibrational state of the water molecules (Mghazli et al, 2017).…”
Section: Moisture Effective Diffusivitysupporting
confidence: 87%
“…All mathematical models evaluated had R 2 values higher than 0.90 and can be used to predict satisfactorily the drying kinetics of the samples of the two drying processes, of cowpea bean. Santos et al (2014) studied the drying of residues of 'urucum' (Bixa orellana) grains by direct exposure to the sun combined with drying in heat accumulator dryer and obtained good results in the fitting of the models. Doymaz (2011) studied sun drying of okra and also obtained good fits using the models employed in the present study.…”
Section: Resultsmentioning
confidence: 99%
“…Studies to overcome such inconvenience should consider the accumulation of solar energy during the day in order to maintain the drying during the night, though at a lower rate (Tripathy & Kumar, 2009;Queiroz et al, 2011;Santos et al, 2014). Hence, the use of water to accumulate solar energy during the day has the advantage of allowing the utilization of a relatively small volume of liquid and simple solar collectors.…”
Section: Introductionmentioning
confidence: 99%
“…Atualmente, tal subproduto tem sido estudado pelas suas potencialidades para fins alimentares alternativos na pecuária podendo reduzir custos na produção animal; notadamente, alguns estudos estão relacionados às suas potencialidades para incorporação da alimentação humana (Santos et al, 2014).…”
Section: Introductionunclassified